24.9k views
2 votes
Multiply the polynomials.
(x+ 2)(2x2 + 9x+8)

User Shambhav
by
5.4k points

2 Answers

1 vote

Answer:

2x³ + 13x² + 26x + 16

Explanation:

(x+ 2)(2x² + 9x+8)

= 2x²(x) + 9x(x) +8(x) + 2x²(2) + 9x(2) +8(2)

= 2x³ + 9x² +8x + 4x² + 18x + 16

= 2x³ + 13x² + 26x + 16

User Moreira
by
4.4k points
6 votes

Answer:

2x³ + 13x² + 26x + 16

Explanation:

(x+ 2)(2x² + 9x+8)

= 2x²(x) + 9x(x) +8(x) + 2x²(2) + 9x(2) +8(2)

= 2x³ + 9x² +8x + 4x² + 18x + 16

= 2x³ + 13x² + 26x + 16

User AmitA
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.